(untitled) - Prof. Dr. Tillmann Bartsch; Prof. Dr. Klaus Boers; Prof. Dr. Dr. Hauke Brettel; Prof. Dr. Heinz Cornel; Prof. Dr. Frieder Dünkel; Prof. Dr. Andreas Eicker; Prof. Dr. Stefan Harrendorf; Prof. Dr. Katrin Höffler; Prof. Dr. Daniela Hunold; PD Dr. Johannes Kaspar; Prof. Dr. Joachim Kersten; Prof. Dr. Jörg Kinzig; et al. (NK Neue Kriminalpolitik, 2024)
Neue Kriminalpolitik brings together all disciplines in criminal law – it is the forum for criminal science, law and practice. The journal sees its priority in setting new standards and in providing a forum for interdisciplinary discussions which, including the knowledge from different countries, pursue the following targets: rational approach towards crime, the protection of the fundamental rights, the priority of social self-regulation and conflict solving while reducing state involvement. The journal addresses criminologists, sociologists, lawyers, teachers, forensic psychiatrists and psychologists working in various kinds of fields such as politics and science. Website: www.nk.nomos.de